2021
DOI: 10.1016/j.clinbiochem.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry tests in hospitalized COVID-19 patients: Experience from a Canadian tertiary care centre

Abstract: Background Coronavirus Disease 2019 (COVID-19) has variable clinical presentation, from asymptomatic to severe disease leading to death. Biochemical markers may help with management and prognostication of COVID-19 patients; however, their utility is still under investigation. Methods A retrospective study was conducted to evaluate alanine aminotransferase, C-reactive protein (CRP), ferritin, lactate, and high sensitivity troponin T (TnT) levels in 67 patients who were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Recent studies have reported that patients with severe and/or critical COVID-19 have significantly more abnormal liver biochemistry on admission than do patients with less severe disease [ 6 , 13 ] and that high aminotransferase concentrations on admission predict all-cause mortality, especially in patients with severe disease [ 14 ]. However, few studies have investigated the diagnostic and prognostic value of abnormal laboratory findings [ 15 , 16 ]. Therefore, we examined the associations between liver injury and COVID-19 disease severity and comorbidity by analyzing laboratory test results throughout the duration of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that patients with severe and/or critical COVID-19 have significantly more abnormal liver biochemistry on admission than do patients with less severe disease [ 6 , 13 ] and that high aminotransferase concentrations on admission predict all-cause mortality, especially in patients with severe disease [ 14 ]. However, few studies have investigated the diagnostic and prognostic value of abnormal laboratory findings [ 15 , 16 ]. Therefore, we examined the associations between liver injury and COVID-19 disease severity and comorbidity by analyzing laboratory test results throughout the duration of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Patients having COVID-19 symptoms show a high concentration of in ammatory markers like C-reactive protein, creatinine phosphate kinase, lactate dehydrogenase and alanine aminotransferase showing an increase in value (Rutledge et al, 2021). C-receptive protein, lactate dehydrogenase and neutrophils were raised in critical patients, and lymphopenia than in negative cases (Fan, 2020) (Fan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On March 31, 2020, World Health Organization announced the public health emergency action plan and takes necessary measures to combat COVID-19. The positive cases may be symptomatic, non-symptomatic, or severely ill (Rutledge et al, 2021). COVID-19 affects the respiratory tract along with other organs including the gastrointestinal system, liver, heart, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Patients having COVID-19 symptoms show a high concentration of inflammatory markers like C-reactive protein, creatinine phosphate kinase, lactate dehydrogenase and alanine aminotransferase showing an increase in value (Rutledge et al, 2021). C-receptive protein, lactate dehydrogenase and neutrophils were raised in critical patients, and lymphopenia than in negative cases (Fan, 2020) (Fan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On March 31, 2020, World Health Organization announced the public health emergency action plan and takes necessary measures to combat COVID-19. The positive cases may be symptomatic, non-symptomatic, or severely ill (Rutledge et al, 2021).…”
Section: Introductionmentioning
confidence: 99%